MR Continuously Variable Transmission Driven by SMA for Centrifugal Fan in Nuclear Power Plant - Jianzuo Ma; Hongyu Shu; Jin Huang (Science and Technology of Nuclear Installations)
The running efficiency of centrifugal fan affects the economical efficiency of the ventilation system. In this paper, we proposed a continuously variable transmission system based on magnetorheological fluid and shape memory alloy for improving the operating efficiency of the centrifugal fan. The equation of transmission torque developed by magnetorheological fluid is derived to compute the torque transmission ability in the continuously variable transmission system. A shape memory alloy spring actuator is designed to control the electric current in coil assembly. The results indicate that the change of temperatures has a tremendous influence on the electric current in coil assembly, the transmission torque of the continuously variable transmission system changes rapidly according to the temperatures acting on shape memory alloy spring actuator, and the output angular velocity of the centrifugal fan can be adjusted continuously.